IMPLEMENTASI ASAS TADARRUJ DALAM KONVERSI BANK KONVENSIONAL MENJADI BANK SYARIAH - Mu'tashim Billah; Vivi Rahma; Abdul Mughits; Irma Suryani (IAIN Syekh Nurjati Cirebon, 2023)
AbstractThe efforts to implement Islamic sharia in Indonesia are entering a new phase. This effort can be seen clearly in the trend of the conversion of conventional banks toward Islamic banks. However, there is one thing that hinders this conversion process, namely the status of conventional bank capital which is also converted into Islamic bank capital. This article attempts to describe the problems of the conversion of conventional banks toward Islamic banks. This article is a literature research with a qualitative approach. The method used in this article is normative-juridical by utilizing the concept of tadarruj in the principle of application of Islamic law as an analytical tool. This article argues that conversion is one of several mechanisms for changing a conventional banking institution into an Islamic bank accompanied by a change in the conventional management system into a sharia system. In the conversion process, all conventional bank transactions are converted into transactions with sharia nuances. This change in contract only has implications for the principal of the contract, without including the margin and interest that are characteristic of conventional banks.Keywords: the conversion; conventional bank; islamic bank; tadarruj